Exploring the Relationship Between ESG Performance and Green Bond Issuance - Wang, Shanshan; Wang, Derek (Frontiers in Public Health, 2022)
As an important part of green financial instruments, green bonds have become increasingly popular in recent years. This study employs green bond issuance as a proxy to measure investors' recognition of a firm's sustainable activities by linking literature on ESG and financial performance and those on green bond issuance. This study innovatively creates the datasets by combining the ESG performance of Chinese listed companies with their green bond issuance from 2016 to 2020 based on the Wind and CSMAR databases and examines the relationship between the performance of ESG dimensions and green bond issuance from the perspective of listed firms in the emerging market. The results indicate that decent ESG practices not only increase the propensity in green bond issuance by listed firms but also help them issue more green bonds. More specifically, we found evidence to support this finding from every dimension of these sustainable practices. However, this study identified the negative effect of financial performance in issuing green bonds when combining the effect of ESG performance.